Enantioselective Hydrogenation of Ethyl Pyruvate Catalyzed by 1,2-Diphenyl-ethylenediamine-Modified Iridium Complex: Effect of Solvent - Du, You; Li, Chun; Tan, Xiaoyun; Fu, Haiyan; Zheng*, Xueli; Li, Ruixiang; Chen*, Hua (Asian Journal of Chemistry, 2014)
The enantioselective hydrogenation of ethyl pyruvate was explored by a readily available homogeneous iridium catalysis system. It was found that (1R,2R)-(+)-1,2-diphenyl-ethylenediamine [(1R,2R)-DPEN] modified [Ir(COD)Cl]2 (COD = cis,cis-1,5-cyclooctadiene) was highly active for the enantioselective hydrogenation of ethyl pyruvate, and the moderate enantioselectivity of 29 % was obtained (the best value reported by iridium catalysts was 39 %). NMR spectroscopy proved that hydrogen bond between the solvent and the a-carbonyl of ethyl pyruvate would be favor to the enantioselective hydrogenation.